In Vitro Effects of Urokinase — Prevention by Different Inhibitors - Oethinger, M D; Seifried, E (Thrombosis and Haemostasis, 1990)
The present in vitro study investigated dose-, time- and temperature-dependent effects of two-chain urokinase plasminogen activato(u-PA, urokinase) on normal citrated plasma. When 10 μg/ml u-PA wereadded to pooled normal plasma and incubated for 30 min at an ambient temperature (25° C), α2-antiplas-min decreased to 8% of the control value. Incubation on ice yielded a decrease to 45% of control,whereas α2-antiplasmin was fully consumed at 37° C. Fibrinogen and plasminogen fell to 46% and 39%, respectively, after a 30 min incubation at 25° C. Thrombin time prolonged to 190% of control.Various inhibitors were studied with respect to their suitability and efficacy to prevent these in vitro effects. Aprotinin exhibited a good protective effect on fibrinogen at concentrations exceeding 500 KlU/ml plasma. Its use, however, was limited due to interferences with some haemostatic assays. We could demonstrate that L-Glutamyl-L-Glycyl-L-Arginyl chloromethyl ketone (GGACK) and a specific polyclonal anti-u-PA-antibody (anti-u-PA-IgG) effectively inhibited urokinase-induced plasmin generation without interfering with haemostatic assays. The anti-u-PA-antibody afforded full protection ofα2-antiplasmin at therapeutic levels of u-PA.It is concluded that u-PA in plasma samples from patients during thrombolytic therapy may induce in vitro effects which should be prevented by the use of a suitable inhibitor such as GGACK or specific anti-u-PA-antibody.